Development of an Interactive E-Module on the History of Quantum Physics Assisted by Flip PDF Professional - Anggita Dewi Mithasari; Silvia Laeli; Muhamad Mi’da Farkhan; Rida Siti Nur’aini Mahmudah (Jurnal Penelitian Pendidikan IPA, 2024)
The rapid development of technology greatly affects the education system in Indonesia, especially in the use of Information Technology (IT) devices such as hardware and software in the teaching and learning process. This research focuses on developing interactive e-modules using the Flip PDF Professional application to improve students' quantum physics learning experience. This research problem addresses the difficulties faced by students in understanding quantum physics concepts, which leads to low academic achievement. This study aims to assess the feasibility and user satisfaction of the interactive e-module "History of Quantum Physics" developed with the help of the Flip PDF Professional application. The research method used is ADDIE (Analyse, Design, Development, Implementation, Evaluation) which involves validation by material experts and trials on physics education students at two universities. The results showed that the feasibility of interactive e-modules of quantum physics history by media and material experts obtained results that were feasible to be tested without revision with a percentage of 81.8%. So that the e-module can be tested on undergraduate and postgraduate physics education students. User satisfaction test results show that e-modules can be used as a support for quantum physics learning media with a satisfaction percentage of 91.33% or very satisfied.